(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
In law, crime and punishment is entirely based on criminal responsibility and this in turn depends on the age of a person. It is well known that appearance and fusion of epiphysis of long bone occurs at particular period of time and this in turns help in age estimation. As there is variation in appearance and fusion time of epiphysis, aim of the present study is to determine Epiphyseal union of proximal end of humerus in boys in Ahmedabad region. Present study was conducted by department of Forensic Medicine and Toxicology, B.J. Medical College Ahmedabad. Total 100 boys of age group between 14-20 years were included in the study and were subjected for radiological examination. To study the appearance and fusion of ossification centre of upper end of humerus digital X-ray with AP view was taken. Result was tabulated and statistical analysis of result was done comparing with previous studies.